My Woman His Wife 3 : Playing for Keeps - J., Anna (Deer Park, NY : Urban Books, 2012)
Four years after disrupting the Cinque family, Monica is back to cause some more trouble, but with enemies everywhere, she has to decide if she wants to stay in Philadelphia or return to Atlanta where she thinks she will be safe.
Keywords: African Americans -- Fiction; Triangles (Interpersonal relations) -- Fiction; African American lesbians -- Fiction